THE USE OF VISUAL MNEMONIC TECHNIQUE IN TEACHING ACTIVE VOCABULARY AT THE TENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL 2 GOWA - Nurinsani Nurinsani; Indah Fadhilah Rahman; Muhammad Syahruddin Nawir (International Conference on Social and Islamic Studies, 2021)
Vocabulary is an indispensable part of language and it is importance for second language learners. Nowadays, however, researchers have realized that vocabulary is an important part of language learning and teaching, worthy of attention and research. This paper provides information on how Visual Mnemonic can be used as one of the best technique to improve vocabulary learning, recall, and boost memory. This study was aimed to examine whether or not the use of Visual Mnemonic Technique effective in teaching vocabulary. The researcher epmloyed quasi experimental design by using non-equivalent control group design and took 2 classes in this research. The data were collected by using instrument with pre-test and post-test. The result of this research was analyzed by SPSS program. This program began with normality test, paired t-test to calculate the mean score, standard deviation, score of t-count and significant (2-tailed). The final results of this study showed that, null hypothesis was rejected while the alternative hypothesis was accepted. Visual Mnemonic Technique effective and improved the storage of new information also help the students learn faster and recall better.